COVID-19 and Brazilian handball coaches: impacts on training prescription and professional learning - Vinicius da Silva Musa; Walmir Romário dos Santos; Rodolfo Pombo Menezes; Valter Costa; Rodrigo Aquino; Rafael Pombo Menezes (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aims: This study aimed to analyze the influences of social isolation on the professional performance of Brazilian handball coaches and their expectations for the return of training sessions. Methods: Fifty-two handball coaches participated in this study (Mage=37.4 years; SDage=8.4), who coach U-8 to adult teams, and answered an online survey divided into two main sections: a) coaches' actions with athletes and/or teams throughout social isolation; b) professional learning during social isolation. Descriptive statistics were used for quantitative data analysis and Thematic Analysis for qualitative data analysis. Results: The coaches mentioned that the contact with the teams has been made mostly with WhatsApp (94.2%) and Google Meet or Zoom (75.0%), in which coaches mainly emphasize physical fitness (69.2%) and tactical knowledge (67.3%). For professional learning, coaches are participating in online lectures (96.2%), and virtual meetings (92.3%). Coaches also seek content mainly related to teaching approaches (82.7%), and specific handball exercises (75.0%). Regarding expectations after the social isolation, coaches reported concern about uncertainties for sports practice (restriction of physical contact, decreased incentives for teams, and competitions) and possible psychological benefits (motivation to practice, overcoming difficulties, and learning new resources). Conclusion: The coaches revealed the concern about maintaining the athletes' performance during the social isolation, the uncertainties for the future of the teams, and the difficulties to use different resources for training. We suggested that the courses for coaches emphasize aspects that enable the learning of new technologies (e.g. social networks, video edition, and research platforms).